Large-scale meta-analysis of interleukin-1 beta and interleukin-1 receptor antagonist polymorphisms on risk of radiographic hip and knee osteoarthritis and severity of knee osteoarthritis. - Kerkhof, H; Doherty, M; Arden, N; Abramson, S; Attur, M; Bos, S; Cooper, C; Dennison, E; Doherty, SA; Evangelou, E; Hart, D; Hofman, A; et al. (2011)
OBJECTIVE: To clarify the role of common genetic variation in the Interleukin-1β (IL1B) and Interleukin-1R antagonist (IL1RN) genes on risk of knee and hip osteoarthritis (OA) and severity of knee OA by means of large-scale meta-analyses. METHODS: We searched PubMed for articles assessing the role of IL1B and IL1RN polymorphisms/haplotypes on the risk of hip and/or knee OA. Novel data were included from eight unpublished studies. Meta-analyses were performed using fixed- and random-effects models with a total of 3595 hip OA and 5013 knee OA cases, and 6559 and 9132 controls respectively. The role of ILRN haplotypes on radiographic severity of knee OA was tested in 1918 cases with Kellgren-Lawrence (K/L) 1 or 2 compared to 199 cases with K/L 3 or 4. RESULTS: The meta-analysis of six published studies retrieved from the literature search and eight unpublished studies showed no evidence of association between common genetic variation in the IL1B or IL1RN genes and risk of hip OA or knee OA (P>0.05 for rs16944, rs1143634, rs419598 and haplotype C-G-C (rs1143634, rs16944 and rs419598) previously implicated in risk of hip OA). The C-T-A haplotype formed by rs419598, rs315952 and rs9005, previously implicated in radiographic severity of knee OA, was associated with reduced severity of knee OA (odds ratio (OR)=0.71 95%CI 0.56-0.91; P=0.006, I(2)=74%), and achieved borderline statistical significance in a random-effects model (OR=0.61 95%CI 0.35-1.06 P=0.08). CONCLUSION: Common genetic variation in the Interleukin-1 region is not associated with prevalence of hip or knee OA but our data suggest that IL1RN might have a role in severity of knee OA.